Homo faber or homo credente? What defines humans, and what could Homo naledi contribute to this debate? - Tönsing, Detlev L. (HTS teologiese studies, 2017)
The transition from pre-human to human has, for a long time, been associated with tool use and construction. The implicit self-definition of humans in this is that of planned control over life world. This is reflected on in the work of Hanna Arendt on the homo faber and the novel by Max Frisch of that name. However, this definition has become problematic in a number of ways: Planned tool use has been seen to occur outside the human species, and the focus on control of the environment has become suspect because of the environmental crisis. The burial practices of Homo naledi indicate high-level self-awareness and social communication, with little tool use being evident. This article asks whether this might be an occasion to redefine our conception of what it means to be human away from the focus on mastery and control and towards including trust, also religious trust, as the true mark of humanity.